2009
DOI: 10.1088/0022-3727/42/9/095104
|View full text |Cite
|
Sign up to set email alerts
|

Electric transport properties of Mn12-acetate films measured with self-assembling tunnelling junction

Abstract: Electric transport properties of Mn12-acetate films have been measured with a self-assembling tunnelling junction device at a liquid helium temperature of 4.2 K. For fresh films, clean I–V characteristics including the zero bias feature and the stair-case like I–V curves are observed. For stored films, however, all those features disappear and ‘telegraph’ noise appears, which indicate the deterioration of the Mn12-acetate molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Elemental analysis: Anal. calcd for C 71 H 120 O 28 Ru 6 N 2 : C,41.97;H,5.88;N,1.36. Found: C,42.77;H,6.02;N,1.56. Note: As the yield of the reaction was significantly low, we eluted further and identified that various other products are also formed in the reaction.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elemental analysis: Anal. calcd for C 71 H 120 O 28 Ru 6 N 2 : C,41.97;H,5.88;N,1.36. Found: C,42.77;H,6.02;N,1.56. Note: As the yield of the reaction was significantly low, we eluted further and identified that various other products are also formed in the reaction.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…calcd for C 71 H 120 O 28 Ru 6 N 2 : C,41.97;H,5.88;N,1.36. Found: C,42.77;H,6.02;N,1.56. Note: As the yield of the reaction was significantly low, we eluted further and identified that various other products are also formed in the reaction. For example, the second fraction of the column is identified as a hexanuclear cluster with the molecular formula of [Ru 6 III (O) 2 (μ-OH) 2 (t-BuCO 2 ) 12 (pyridine) 2 ] (4, yield = 5%) which was reported by us earlier, 14b and the third major fraction from the column is an oxo-centered Ru(III) triangle with the general molecular formula [Ru 3 (O)(t-BuCO 2 ) 6 (pyridine) 3 ] + (m/z = 1164.15 g/mol; yield = 37.1%; vide inf ra).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In the last few decades, molecular materials have been proposed as plausible alternatives for the miniaturization of components for information storage devices. [1][2][3][4][5] Molecules represent the well-defined minimum size limit, [6][7][8][9][10] along with additional advantages when compared with the more common top-down approach: solid state materials typically lose their bulk properties at the nanoscale. [11][12][13] Molecule-based alternatives to optical, 14,15 electric 16,17 or magnetic 18,19 materials have been studied with excellent perspectives, including multifunctional materials exhibiting tailor-made combinations of the abovementioned materials.…”
Section: Introductionmentioning
confidence: 99%